KECEPATAN MEMBACA ARAB MELAYU ANTARA KELAS 2020 A DAN 2020 C PROGRAM STUDI PENDIDIKAN BAHASA DAN SASTRA INDONESIA UNIVERSITAS RIAU - Khairunnisa Syafna Putri; Supiah; Dwi Jonanda Putri; Hasnah Faizah (Universitas 45 Surabaya, 2022)
This study aims to determine the level of students' reading speed. The samples in this study were Class A and C students of the Indonesian Language and Literature Study Program, Faculty of Teacher Training and Education, University of Riau. The data analysis technique is a test technique. Quantitative data analysis techniques were used to analyze the results of the reading speed reading test in Arabic Malay. The data analysis procedure was to measure students' reading speed in reading Malay Arabic texts. Based on the research results, it was found that the reading speed of 2020 A students was 52.58 kpm and that of 2020 C students was 52.65 kpm. This shows that reading speed is still below the standard for student reading speed in the Malay Arabic reading form, which is 200 kpm. Thus, it can be concluded that students tend to read slowly to reduce reading errors, so that their reading speed is below standard.